2000
DOI: 10.1063/1.481742
|View full text |Cite
|
Sign up to set email alerts
|

Freezing and melting of methanol in a single cylindrical pore: Dynamical supercooling and vitrification of methanol

Abstract: Articles you may be interested inOn the state of water in 2.4 nm cylindrical pores of MCM from dynamic and normal specific heat studies J. Chem. Phys. 139, 064507 (2013); 10.1063/1.4817333 Heat capacity of tetrahydrofuran clathrate hydrate and of its components, and the clathrate formation from supercooled melt Universal scaling, dynamic fragility, segmental relaxation, and vitrification in polymer melts Melting/freezing behavior of a fluid confined in porous glasses and MCM-41: Dielectric spectroscopy and mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 22 publications
3
61
0
Order By: Relevance
“…Such depression of the phase transition temperatures has been reported in literature to be characteristic of confined molecules in porous materials. [711][712][713][714][715][716] Remarkably, IB solidified in a glassy state and in a crystalline form when confined in MCM-41 35 and MCM-41 116 , respectively. Authors attributed these two radically different behaviors to steric effects; that is, crystalline ibuprofen is a dimer with a total length of  26 Å so that pores of 116 Å diameters were large enough to allow nucleation of crystallites, whereas pores of 35 Å diameters, even if the dimer fitted inside, were exceedingly constrained, thus inducing a vitrification process.…”
Section: Interaction With Drugs and Natural Productsmentioning
confidence: 99%
“…Such depression of the phase transition temperatures has been reported in literature to be characteristic of confined molecules in porous materials. [711][712][713][714][715][716] Remarkably, IB solidified in a glassy state and in a crystalline form when confined in MCM-41 35 and MCM-41 116 , respectively. Authors attributed these two radically different behaviors to steric effects; that is, crystalline ibuprofen is a dimer with a total length of  26 Å so that pores of 116 Å diameters were large enough to allow nucleation of crystallites, whereas pores of 35 Å diameters, even if the dimer fitted inside, were exceedingly constrained, thus inducing a vitrification process.…”
Section: Interaction With Drugs and Natural Productsmentioning
confidence: 99%
“…17 Crystallisation of bulk methanol cannot be avoided at low temperature so that the glassy state is unreachable with usual quenching rates. However, a glass transition has been reported for methanol deposited on a cold substrate from its vapour phase.…”
Section: /33mentioning
confidence: 99%
“…15,16 Phase transitions of methanol confined in regular cylindrical pores of MCM-41 and SBA-15 silicates have been investigated by X-rays diffraction. 17 The freezing/melting behavior depends markedly upon the pore size, with different degrees of hysteresis and metastability. Within the pores of diameter lower than 78 Å, crystallization never occurs and the confined methanol ultimately vitrifies at about 100 K close to the value of the bulk glass transition temperature.…”
Section: Introductionmentioning
confidence: 99%
“…We know from theory of phase transitions (24) and experimental observations (25) that freezing of a liquid (or in fact any first-order phases transition) is rounded in a microscopic cylindrical (onedimensional) pore and the phase change becomes more obscure as the diameter decreases. In nanopores, however, freezing behavior is not simply explained by the general ''rounded-off'' picture but differs from one system to another and can be much richer than that in larger pores (18,26). An earlier MD simulation study showed that water in carbon nanotubes may freeze either continuously or discontinuously, depending on diameter and pressure (11).…”
mentioning
confidence: 99%